Vrednost izmenjenih metilacionih obrazaca gena RANBP3, LCP2 i GRAP2 u CFDNA u dijagnozi raka dojke: Altered Methylation in cfDNA for Breast Cancer Diagnosis - Hu, Qin; Mao, Yu; Lan, Haomiao; Wei, Yi; Chen, Yuehua; Ye, Qiang; Che, Hongying (Journal of Medical Biochemistry, 2023)
Background: The purpose of this study was to investigate the potential of plasma cfDNA methylation patterns in reflecting tumor methylation changes, focusing on three candidate sites, cg02469161, cg11528914, and cg20131654. These sites were selected for verification, with a particular emphasis on their association with breast cancer. Methods: We conducted a comprehensive analysis of 850k whole-methylation sequencing data to identify potential markers for breast cancer detection. Subsequently, we examined the methylation status of genes RANBP3, LCP2, and GRAP2, where the aforementioned sites are located, using cancer and cancer-adjacent tissues from 17 breast cancer patients. We also assessed the methylation patterns in different molecular subtypes and pathological grades of breast cancer. Additionally, we compared the methylation levels of these genes in plasma cfDNA to their performance in tissues. Results: Our analysis revealed that RANBP3, LCP2, and GRAP2 genes exhibited significant methylation differences between cancer and cancer-adjacent tissues. In breast cancer, these genes displayed diagnostic efficiencies of 91.0%, 90.6%, and 92.2%, respectively. Notably, RANBP3 showed a tendency towards lower methylation in HR+ breast cancer, and LCP2 methylation was correlated with tumor malignancy. Importantly, the methylation levels of these three genes in plasma cfDNA closely mirrored their tissue counterparts, with diagnostic efficiencies of 83.3%, 83.9%, and 77.6% for RANBP3, LCP2, and GRAP2, respectively. Conclusions: Our findings suggest that RANBP3, LCP2, and GRAP2 genes, located at the identified methylation sites, can serve as valuable blood molecular markers for the auxiliary diagnosis of breast cancer. This research provides a foundation for further exploration of gene methylation pattern changes in cfDNA for the detection of breast cancer and other cancer types.